‘If I just get one IELTS certificate, I can get anything’: an impact study of IELTS in Pakistan - Memon, Natasha (The University of Edinburgh, 2015)
This thesis examines the impact of the high-stakes International English Language Testing System (IELTS) across different stakeholders in Pakistan, and on Pakistani education, society and economy more broadly. The global profile of IELTS means that washback and impact studies (both comparative and country-specific) are now increasingly carried out by Cambridge ESOL (Hawkey, 2006; Moore et al., 2012). These are undertaken not simply with a view to improving the test, but with a view to investigating how it is used and perceived. In Pakistan, as elsewhere, IELTS has assumed great significance on account of its gate-keeping function in emigration, higher education abroad and professional registration. Demand and candidature grow daily. However, specific conditions that pertain in Pakistan, mainly political instability, and major disparities in wealth and development, have a particular effect on the role of IELTS in the country. The current impact study employs a sequential exploratory concurrent embedded mixed methods design to assess the impact. Phase 1 is a preliminary survey of 20 IELTS preparation institutes, followed by an in-depth qualitative study of two IELTS preparation centres. The qualitative study employs classroom observations, semistructured interviews with teachers (N=2), informal conversational interviews with test-preparers (N=20), and pre- and post-study testing to assess the efficacy of IELTS preparation. Phase 2 analyses questionnaires from a further ten preparation centres. Respondents comprised 200 IELTS test-preparers, 100 IELTS test-takers and 10 IELTS preparation teachers. The survey was supplemented by a focus group with four test-preparers and semi-structured interviews with five employers and five parents. The initial survey of the private English Language Teaching industry in Pakistan showed a radical expansion of IELTS preparation courses. Yet the in-depth study of two specific centres showed that the courses are not effective in improving the scores of students. Courses, although relatively expensive, are very short and most testpreparers enter them with lower English proficiency than is appropriate for IELTS. Questionnaires and interviews showed that IELTS test-preparers and test-takers are primarily motivated to take the test for emigration and study abroad. The test preparers have high expectations from the course regarding improvement of their English proficiency which are generally not met. Disappointed test-takers hold some beliefs that their IELTS course and test will be of benefit to them in Pakistan. Although English ability is always considered as part of recruitment, employers interviewed for this project confirmed that an IELTS certificate is never explicitly required. It is likely that the local uses of IELTS that are emerging in Pakistan are much more indirect. I argue that because public education is not meeting the demand for English, IELTS is now perceived as a route of English education and general certification, and a badge of middle class status if not actual material gain. These findings have implications for both providers of state education in Pakistan, and providers of the IELTS test (Cambridge ESOL). The former needs to address the lack of publicly funded English education and English qualifications; and the latter needs to consider whether IELTS is appropriate for large numbers of low proficiency candidates, and for purposes other than admission to universities abroad and immigration.
Keywords: impact; washback; english language testing